FLUID REGIME OF DIAMOND CRYSTALLISATION IN CARBONATE-CARBON SYSTEMS - Sokol A.G.; Tomilenko A.A.; Pal'yanov Y.N.; Borzdov Y.M.; Pal'yanova G.A.; Khokhryakov A.F. (My University, 2000)
The gaseous phase in experiments of diamond crystallisation in the carbonate-carbon systems Li2CO3-C, Na2CO3-C, K2CO3-C, Cs2CO3-C, CaCO3-C, CaMg(CO3)2-C at P = 7 GPa and T =1 700-1750°C (using the 'split-sphere' high-pressure device) was studied by means of gas chromatography. Unlike in traditional metal-carbon systems, in which diamond forms under highly reducing conditions in the presence of a methane-hydrogen fluid, crystallisation of diamond in carbonate-carbon systems occurs in the presence of a H2O-CO2-rich fluid. The results provide experimental confirmation of the possibility for diamond to crystallise in nature in a wide range of redox conditions.